9. Difference in cholesterol levels hunter dog (Canis familiaris) with dog house in the district of Lima Puluh Kota - Angga Putra Adinata; Rusli Rusli; Amiruddin Amiruddin; Nuzul Asmilia; Sri Wahyuni; Roslizawaty Roslizawaty (Jurnal Medika Veterinaria, 2018)
The aims of this study to find out differences in cholesterol levels hunter dog and dog house in the district of Lima Puluh Kota. This study using 99 hunter dogs and 98 dogs home in a healthy condition clinically. Dog blood samples were taken on the morning at the cephalika venous. Blood samples were obtained dripped on cholesterol strip that has been put into Gluco-dr and after 10 seconds cholesterol levels can read on screen. Data were analyzed statistically using chi-square test T which were helped by SPSS 16. The results showed that the average cholesterol levels in the dogs hunt were 87.67 ± 43.49 mg / dl and 297 in the dogs house, 72 ± 94 mg / dl. The statisticresult was showed significant difference (p 0.05) between blood cholesterol levels with a hunter dogs anddogshouse blood cholesterol levels. This research can be concluded that average of cholesterol levels of hunter dogs and dogs house were still within the normal range, but showed the sicnificant differences due to the different activities of dogs.